„Antypolska akcja” OUN-UPA na Wołyniu i w Galicji Wschodniej - Grelka, Frank M. (Pamięć i Sprawiedliwość, 2004)
The intention of this study is to outline the problematical context of the massacres of Polish residents by armed forces – UPA (Ukrainian Insurgent Army) of OUN (Organization of Ukrainian Nationalists) in Volhynia and Eastern Galicia in 1943 and 1944. By taking into consideration both historical background and the immanent context of the events which led to the outburst of violence in the Polish-Ukrainian borderland, it attempts to look beyond the well-known facts.In addition, the „anti-Polish action”, as a paradigm of relations between two nations, needs a revised evaluation of Polish-Ukrainian relations next to the tragic events in Volhyniaand Eastern Galicia of 1943 and 1944. Gaining deeper insight into the reasons of this mass murder, a synthesis of multiethnic interaction in these regions throughout the 19th and 20th centuries is exposed:– The social, ideological and political roots of OUN built the framework of nationalism regarding the pre-war Polish policy towards Ukrainians;– The fundamental impact of nationality policy by Germany in occupied Volhynia and Galicia, cultural Ukrainization and the maintenance of traditional administrative relations for purposes of economic exploitation;– The OUN as a factor of the German policy of ethnic cleansing, while attacking Soviet Union, and its consequences for the future warfare of UPA in Eastern Poland;– The „anti-Polish action” of OUN-UPA and the strategy of ethnic cleansing against the Polish civilian population in the frame of the German-Soviet partisan war about Volhynia and Eastern Galicia.Apart from the Polish-Ukrainian historiography of the issue at hand, this paper and its hypotheses intends to serve as a stimulus to new approaches in the area of „Polish-Ukrainianrelations” with reference to the time of Soviet/German occupation of Poland in general and the incidents in Volhynia and Eastern Galicia in particular. The results are rather suggestive than conclusive. They refer to the numerous factors, among them German/Soviet occupation politics or the protest against the Polish Ukrainian politics, which manifest in the „anti-Polish action”. Finally, there is the question to what extent the OUN-UPA at all continued the legacy of the Ukrainian national movement in their efforts for an independent Ukraine.